2016
DOI: 10.1007/978-3-319-22422-0_13
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Peer- and Self-Assessment and Teacher Assessment of Young EFL Learners’ Oral Presentations

Abstract: As the traditional grammar translation approach is being gradually replaced by communicative or task-based approaches, paper-and-pencil tests, commonly used in English classes in Taiwan, do not meet the course goals. Alternative assessment, known for increasing learners' cognitive and meta-cognitive development as well as empowering students to take ownership of their learning, has been practiced extensively in L1 higher education, but neglected in L2 elementary schools. Thus, the purpose of this study is to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…In congruence with previous studies in both L1 contexts (Topping, , ) and L2 contexts (Hung et al, ; Peng, ), the group of students in this study perceived the PA activity positively, and many, especially the fifth graders, could rate their peers as their instructor did. These results, while modest, suggest that PA provides a possible approach to evaluating English learners' speaking performance.…”
Section: Reflectionsupporting
confidence: 89%
See 2 more Smart Citations
“…In congruence with previous studies in both L1 contexts (Topping, , ) and L2 contexts (Hung et al, ; Peng, ), the group of students in this study perceived the PA activity positively, and many, especially the fifth graders, could rate their peers as their instructor did. These results, while modest, suggest that PA provides a possible approach to evaluating English learners' speaking performance.…”
Section: Reflectionsupporting
confidence: 89%
“…Hung, Samuelson, and Chen () examined 69 sixth graders' practice of PA in elementary school in Taiwan. The results showed that group ratings of the students' individual oral report were strongly correlated with the instructor's ratings, except for the criterion content of the presentation .…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Results from the study showed that YLLs are equally sensitive to the onscreen test features/context of the speaking test as they are to the task demands, and called for researchers' and test developers' attention to the onscreen task features that may contribute to YLLs' performances on the speaking tests. Hung et al (2016) investigated the comparability between peer, self-, and teacher assessment of young Taiwanese EFL learners' oral presentation skills as well as student and teacher perceptions of the assessment experience. Sixty-nine sixthgrade students, who were learning English in Taiwan, participated in the study.…”
Section: Assessing Ylls' Oral Language Proficiencymentioning
confidence: 99%
“…While such generic SAs have been readily available for teachers and are often used for young learners, more contextualized SA implementation (e.g., conducting SA immediately after a corresponding task) has gained increasing attention among teachers of young learners (Y. Butler, ; Hung, Samuelson, & Chen, ). Does the degree of context‐embeddedness of SA implementation influence young learners’ processes of responding to SA items?…”
mentioning
confidence: 99%